(-a-b)^2 = (a+b)^2 = a^2 + b^2 + 2*a*b
/т.к. (-a-b)^2 = |-a-b|^2 = |-(a+b)|^2 = |a + b|^2 = (a + b)^2/
(-a-b)^2 = (a+b)^2 = a^2 + b^2 + 2*a*b/т.к. (-a-b)^2 = |-a-b|^2 = |-(a+b)|^2 = |a + b|^2 = (a + b)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
(-a-b)^2 = (a+b)^2 = a^2 + b^2 + 2*a*b
/т.к. (-a-b)^2 = |-a-b|^2 = |-(a+b)|^2 = |a + b|^2 = (a + b)^2/
(-a-b)^2 = (a+b)^2 = a^2 + b^2 + 2*a*b/т.к. (-a-b)^2 = |-a-b|^2 = |-(a+b)|^2 = |a + b|^2 = (a + b)
/т.к. (-a-b)^2 = |-a-b|^2 = |-(a+b)|^2 = |a + b|^2 = (a + b)^2/